SISTEM INFORMASI MANAJEMEN JEMBATAN BERBASIS WEB SEBAGAI PENDUKUNG KEPUTUSAN PENGELOLAAN JEMBATAN - , Bhima Dhanardono; , Akhmad Aminullah, ST., MT., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Bridge Management Information System (BMIS) in Indonesia is facing the problems of easy access to information on bridges, high subjectivity of inspectors and the lack of community participation. This study presents BMIS with data analysis developed from the Interurban Bridge Management System (IBMS). The Analytical Hierarchy Process method used in this study is to determine the weight of each element of the bridge so that the bridge condition assessment can occurs automatically. The treatment priority is determined by condition value (CV) of main elements of the bridge, CV of overall bridge and CV of traffic. The research objects are 25 bridges on 4 road links in Central Java. The research is implemented in www.datajembatan.com which includes an inventory and analysis of national-scale bridge data. By using element weight, element condition input only at level 5. From the 25 bridges studied, the main priority is Juana I with the CV 0.627, estimated service life reaches 11 years with periodic maintenance on the bottom chord element and pile and 7 meters wide bridge duplication